The Md of Adriel’s M(In)D - Alvin Surya Pratama (Institute of Research and Community Outreach - Petra Christian University, 2018)
This creative project is a novel that tells a story about a teenage boy, Adriel, who tries to live of his life on a number of depressing accounts that is happening throughout his life. His father, Julius, has changed Adriel for the worse due to his subconscious abusive actions because he contracts depression himself. Adriel’s depression is going to accumulate based on the inferiority complex, excessive guilt, and other instances he experience along the way. Adriel then meets a girl named Olivia. Olivia is a cheerful, seemingly smart girl on the outside, but Adriel realizes that she is just the same as he is. My purpose of writing this novel are to raise the ever-growing prevalent issue on suicidal depression in our society; to understand why and how someone might feel depressed; and, for people to know the underlying symptoms, so they are not letting it go unnoticed.